FRI0346 Evaluating Differences in The Enrolled Populations of Randomized Clinical Trials of Systemic Lupus Erythematosus. (15th July 2016) - Goel, N.; Barrett, B.; Duncan, A.; Gallagher, M.-B.; Mackey, M.
Abstract : Background: Most randomized controlled trials (RCTs) in systemic lupus erythematosus (SLE) specify specific populations of interest for eligibility, but still vary in the populations included. These differences include the level of baseline disease activity, the relative contribution of clinical vs laboratory disease manifestations, baseline corticosteroid dosage, the presence and number of specific immunosuppressant therapy, antimalarials and racial/ethnic mix. Data have been presented previously highlighting regional differences in SLE populations potentially influencing treatment responses. 1 Objectives: Evaluate the demographics and baseline disease characteristics of randomized SLE patients across three different clinical trials conducted through our organization. Methods: We evaluated combined screening demographic and disease-specific data from three recently conducted SLE studies post hoc. Eligibility criteria were targeted at the enrollment of patients with moderate to severe active SLE (SELENA-SLEDAI ≥8 for two studies of approximately 700 and 850 patients each, and SLEDAI-2K ≥6 for the third study of approx. 300 patients). Two studies were globally recruited, one was regional. Patients with varying degrees of severely active lupus nephritis or neuropsychiatric SLE were excluded. Differences between each combination of two study populations were evaluated via a two-tailed t-test for disease duration, corticosteroid use, immunosuppressant use, C3/C4 and anti-dsDNA status. Results: Of the 1857 randomized patients, 39.3% were white and 93.4% were female. Details regarding treatment medications (corticosteroids, immunosuppressant use and antimalarials), SLEDAI scores (total and clinical); anti-dsDNA, ANA, and C3 and C4 status are presented in the table for the overall population. Mycophenolate (20.0%) was the most common immunosuppressant used, followed by azathioprine (15.8%) and then methotrexate (9.5%). Differences were determined to exist between each study population at the p<0.001 level for the percentage of subjects on corticosteroids, on immunosuppressants (except for a nonsignificant difference in the proportions using concomitant immunosuppressants between the two global studies); with hypocomplementemia, with elevated anti-dsDNA titers or with both. Conclusions: SLE patients enrolled in RCTs, despite having similar levels of disease required by SLEDAI scores, had differences in critical baseline laboratory characteristics as well as in standard of care medications. These differences may have been impacted by regional differences, e.g., treatment standards of care as well as culturally driven behaviors, and study size; and may impact evaluation of the treatment response. Further differences in regional levels of disease activity are being evaluated as a next step. Understanding such differences may influence the design of SLE trials moving forward. References: Furie R, et al. Arthritis Rheumatol. 2015; 67 (suppl 10). http://acrabstracts.org/abstract/geographic-differences-in-demographics-clinical-characteristics-and-standard-of-care-in-multinational-studies-of-patients-with-moderate-to-severe-systemic-lupus-erythematosus/ . Accessed January 29, 2016. Disclosure of Interest: N. Goel Employee of: Quintiles Inc., B. Barrett Employee of: Quintiles Inc., A. Duncan Employee of: Quintiles Inc., M.-B. Gallagher Employee of: Quintiles Inc., M. Mackey Employee of: Quintiles Inc.